Attitude of nursing students towards nursing profession at South Valley University - , Sahar Fahmy; Asmaa Mayez,; Reda Refae Ali, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background : Professionalism is one of the basic principles of nursing and the product of environmental and other interaction. Nursing expertise affects the quality of care and is influenced by a variety of factors.Aims; This study was aimed to explore the perception of outgoing nursing students towards nursing profession and perceived future job orientation.Setting; Faculty of Nursing, South Valley University.Subjects; Convenient sample of nursing students (No. = 290). Tools; consisted of 1) Personal data sheet 2) tool used to explore attitude of nursing profession among associate nursing students 3) questions related to social rank of job, feeling about nursing as a profession, change in nursing image after joining Faculty of Nursing, and Job Prospective.Results; more than half of nurses ' attitude towards nursing careers had negative attitudes. there was a statistically significant difference regarding negative perceptions of nursing profession relevant to male nurses' studentsConclusions; Almost more than half of nurses had negative attitude towards nursing careers. the majority of participant students from male have negative image about nursing profession, Likewise, the highest percentage of both male and female students feel proud when talking about nursing. More than half preferred to work as a nursing administration.Recommendations; Develop and organize a career training system in nursing care. Providing better financial incentives for working conditions. Better financial benefits and career opportunities to encourage graduates to be working in health services.